Upregulation of TCPTP in Macrophages Is Involved in IL-35 Mediated Attenuation of Experimental Colitis - Baoren Zhang; Chenglu Sun; Yanglin Zhu; Hong Qin; Dejun Kong; Jingyi Zhang; Bo Shao; Xiang Li; Shaohua Ren; Hongda Wang; Jingpeng Hao; Hao Wang (Mediators of Inflammation)
Ulcerative colitis (UC) is a chronic intestinal inflammatory disease with complex etiology. Interleukin-35 (IL-35), as a cytokine with immunomodulatory function, has been shown to have therapeutic effects on UC, but its mechanism is not yet clear. Therefore, we constructed Pichia pastoris stably expressing IL-35 which enables the cytokines to reach the diseased mucosa, and explored whether upregulation of T-cell protein tyrosine phosphatase (TCPTP) in macrophages is involved in the mechanisms of IL-35-mediated attenuation of UC. After the successful construction of engineered bacteria expressing IL-35, a colitis model was successfully induced by giving BALB/c mice a solution containing 3% dextran sulfate sodium (DSS). Mice were treated with Pichia/IL-35, empty plasmid-transformed Pichia (Pichia/0), or PBS by gavage, respectively. The expression of TCPTP in macrophages (RAW264.7, BMDMs) and intestinal tissues after IL-35 treatment was detected. After administration of Pichia/IL-35, the mice showed significant improvement in weight loss, bloody stools, and shortened colon. Colon pathology also showed that the inflammatory condition of mice in the Pichia/IL-35 treatment group was alleviated. Notably, Pichia/IL-35 treatment not only increases local M2 macrophages but also decreases the expression of inflammatory cytokine IL-6 in the colon. With Pichia/IL-35 treatment, the proportion of M1 macrophages, Th17, and Th1 cells in mouse MLNs were markedly decreased, while Tregs were significantly increased. In vitro experiments, IL-35 significantly promoted the expression of TCPTP in macrophages stimulated with LPS. Similarly, the mice in the Pichia/IL-35 group also expressed more TCPTP than that of the untreated group and the Pichia/0 group.